POLA INTERFERENSI MORFOLOGIS BAHASA INGGRIS (B1) TERHADAP BAHASA INDONESIA (B2) PADA RAGAM BAHASA TULIS MAHASISWA ASING TINGKAT PROGRAM CLS-UM - Tri Lestari, Laila (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2014)
This study was aimed to describe the interference pattern of morphological English (B1) into Indonesian (B2) on a variety of written language of foreign students at the advanced level CLS-UM program. The particular purpose was to describe the morphological interference of the affixation (prefixes, suffixes, and konfiks) on a variety of written English language (B1) into Indonesian (B2). Interference on the morphological affixation, divided into three, namely the prefixes, suffixes, and konfiks. In the prefix, interference patterns are 1) the application of inflectional affix morpheme {ed} English into Indonesian; 2) the passive form of some sentence structures; 3) the confusion between the prefix {most} to {ber-}; 4) the implementation of past tense V2; and 5) the pattern of implementation have been + -ing. The design of this study was qualitative descriptive. Researcher tried to describe or depict through words systematically and accurately about the events that occurred during the study. The data type in this study consisted of primary and secondary data. Interference analysis results showed the level of mastery of Indonesian foreign student, both in terms of the structure of language and the vocabulary, still needs to be improved further. This occured because of the influence of the control structure B1, B2 so that the control was neglected. Both of grammar, vocabulary, or vocabulary used tend to B1. Language error refers to the deviation rule (structure or grammar) of standard language.